Performance evaluation of ID based authentication methods in the SIP protocol - Kilinc, H. Hakan; Allaberdiyev, Yolguly; Yanik, Tuğrul (My University, 2009)
The SIP authentication mechanism implemented in most applications is the HTTP Digest Authentication. This mechanism is easy to implement and delivers high performance results. But the weaknesses of this authentication method are not acceptable where security is of high concern. The ID based authentication mechanisms do not suffer from the vulnerabilities of secret based authentication schemes. Also they eliminate the burden of a public key infrastructure inherent in certificate based authentication schemes. In this paper we integrated the Elliptic Curve Digital Signature Algorithm, which is a certificate based authentication scheme and the ID based authentication schemes of Hess and Cha-Cheon into a widely used open source SIP proxy server called OpenSIPS and obtained real performance data. The performance results we obtained illustrate that the ID based authentication methods are comparable to certificate based authentication schemes. The advantages of ID based cryptography will increase the use of ID based authentication methods within SIP like protocols in the near future. ©2009 IEEE. © 2010 Elsevier B.V., All rights reserved.
2009 International Conference on Application of Information and Communication Technologies, AICT 2009 -- Baku -- 79447
Keywords: ID based authentication; Performance; Security; Session Initiation Protocol (SIP)